Phytochemical Identification of Secondary Metabolite Compounds in Leaf Extracts of Sente (Alocasia macrorrhizos), Guava (Psidium guajava L.), and Their Combination - Adelia Permata Dewi; Majida Ramadhan; Faisal Faisal; Qonita Mukrimatul Hijjah; Naura Dinada Zulfa Salsabila; Nafisa Nafisa (Biology, Medicine, & Natural Product Chemistry, 2026)
The presence of secondary metabolites in plants plays an important role in their biological activities and supports the use of natural ingredients as candidates for phytopharmaceutical development. This study evaluated the phytochemical profile of ethanol extracts of sente leaves (Alocasia macrorrhizos) and guava leaves (Psidium guajava L.), as well as their combined extract. The extracts were obtained using maceration, followed by qualitative phytochemical screening, UV-Vis spectrophotometry, and FTIR analysis. Physicochemical parameters showed that the moisture content of sente and guava leaves was 4.251% and 4.617%, respectively, while the ash content was 0.97% for sente and 0.59% for guava leaves. The extraction yield of guava leaves (3.81%) was higher than that of sente leaves (2.59%). The results showed that A. macrorrhizos contained flavonoids, tannins, and triterpenoids, whereas P. guajava exhibited a more complete profile, including alkaloids, saponins, flavonoids, tannins, and triterpenoids. The combined extract yielded positive results for almost all tested metabolite groups. The UV-Vis spectra showed absorption peaks in the range of 321–369 nm, while the FTIR spectra revealed the presence of –OH, aliphatic C–H, aromatic C=C, and C–O functional groups. Overall, the findings indicate that both extracts and their combination have strong potential as sources of bioactive compounds and may be further developed for phytopharmaceutical applications.